UJIAKTIVITAS ANTIBAKTERI GRANUL EFFERVESCENT EKSTRAK ETANOL BIJI PEPAYA (Carica papaya L.) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli - Listiani, Putu Ayu Ratih; Dewi, I Dewa Ayu Eka Purnama (Jurnal Kesehatan Farmasi, 2025)
Background: Diarrheal disease in Indonesia continues to increase every year, this has resulted in the use of drugs that continues to increase. Processing of papaya seeds (Carica papaya L.) which is formulated into effervescent granules that can act as a complementary medicine that functions to inhibit the growth of Escherichia coli bacteria that causes diarrhea. Methods: The research method is to test the antibacterial extract and effervescent granule preparationsthat have been formulated with papaya seed extract in inhibiting the growth of Escherichia coli. Results: Papaya seed extract contains alkaloids, flavonoids, saponins, terpenoids and tannins which are capable of providing antibacterial activity in inhibiting the growth of Escherichia coli bacteria. Effervescent granules with concentrations of 1.5%, 2% and 2.5% had inhibition capacities of 18.5 mm, 14 mm and 19.5 mm, respectively.Conclusion: The largest inhibition zone on effervescent granules of papaya seed extract is formulation 3, replication 2.